Does magnification increase total unsharpness in DR radiography?. (October 2017) - Loughman, Eamon; Rowan, Michael; Kenny, Patrick
Abstract : In General Diagnostic Radiography it is generally assumed that an increase in magnification results in a non-linear increase in total unsharpness (Utot). Utot is the sum in quadrature of contributing sources of unsharpness, including geometrical/penumbra (Upen) and detector unsharpness (Udet). However, this assumption is based on traditional film/screen radiography where focal spot sizes of approximately one and two millimetres are considerably greater than the resolution of the film/screen detector. Therefore penumbra (or geometrical) unsharpness (Upen) dominated. However, modern Digital Radiography (DR) imaging systems combine smaller focal spot sizes (typically 0.6 & 1.0 mm), with lower resolution detectors having pixels sizes of approximately 0.15 mm. It is unclear how magnification affects total unsharpness in such systems. The purpose of this study is to record the total unsharpness for a range of imaging arrangements and verify that they are consistent with the calculated total unsharpness (Utot). Images of a Tantalum target in air, located at different distances from the detector, were recorded. Modulation Transfer Function (MTF) values were used to describe the total unsharpness obtained for a variety of focal spot sizes, detector pixel sizes and magnifications. A novel MTF parameter, % fill area below Nyquist, was used to estimate total unsharpness (Utot). The results obtained are surprising to the extent that many of the magnifications in conventional diagnostic radiography improved total unsharpness. This may have consequences in fluoroscopy. Finally, we verified that magnification, as used in mammography, reduces total image unsharpness.